2016
DOI: 10.1128/aac.02974-15
|View full text |Cite
|
Sign up to set email alerts
|

Clarithromycin Leads to Long-Term Survival and Cost Benefit in Ventilator-Associated Pneumonia and Sepsis

Abstract: cIncreasing numbers of admissions for sepsis impose a heavy burden on health care systems worldwide, while novel therapies have proven both expensive and ineffective. We explored the long-term mortality and hospitalization costs after adjunctive therapy with intravenous clarithromycin in ventilator-associated pneumonia (VAP). Two hundred patients with sepsis and VAP were enrolled in a published randomized clinical trial; 100 were allocated to blind treatment with a placebo and another 100 to clarithromycin at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 21 publications
0
27
0
1
Order By: Relevance
“…Yet these agents can produce potentially beneficial immunomodulatory changes in pneumonia. A multicenter, double-blinded study of 200 ICU patients with sepsis and VAP found that adjunctive clarithromycin led to earlier VAP resolution and faster mechanical ventilation weaning [93, 94]. …”
Section: Contemporary Treatment Strategies For Gram-negative Vapmentioning
confidence: 99%
“…Yet these agents can produce potentially beneficial immunomodulatory changes in pneumonia. A multicenter, double-blinded study of 200 ICU patients with sepsis and VAP found that adjunctive clarithromycin led to earlier VAP resolution and faster mechanical ventilation weaning [93, 94]. …”
Section: Contemporary Treatment Strategies For Gram-negative Vapmentioning
confidence: 99%
“…The use of macrolides dramatically improved the prognosis of patients with diffuse panbronchiolitis. Furthermore, clarithromycin lengthened the survival in patients with ventilator‐associated pneumonia and sepsis and shortened the time to the resolution of infection among patients with pyelonephritis, intra‐abdominal infections, and Gram‐negative bacteremia . The mechanisms by which macrolides improve these diseases remain to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Five evaluations examined antibiotic interventions [22][23][24][25][26], two examined fluid therapies [27,28], eight examined EGDT or other (primarily emergency department [ED]-based) resuscitation protocols [35][36][37][38][39][40][41][42]71], three examined procalcitonin algorithms [29][30][31], two examined immunoglobulin therapies [32][33][34], four examined methods of pathogen identification [43][44][45][46], one examined point of care lactate testing [47], and one examined immediate ICU admission [48]. The remaining 20 evaluations examined interventions no longer used in clinical practice-13 examined drotrecogin alfa (activated) (51-64), and seven examined monoclonal antibodies [64][65][66][67][68][69][70].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The reporting quality varied widely, with scores ranging from 13% (3/23) [65] to 95% (21/22) [42,50]. Twelve (26%) of the studies were found to be of excellent [22][23][24][25][26] Fluid therapies 2 (4%) [27,28] Procalcitonin algorithms 3 (7%) [29][30][31] Immmunoglobulin therapies 2 (4%) [32][33][34] EGDT or other sepsis protocol 8 (17%) [35][36][37][38][39][40][41][42][43] Pathogen identification 4 (9%) [44][45][46][47] Other 2 (4%) [48,49] Interventions no longer in clinical practice reporting quality, 18 (39%) of very good quality, 11 (24%) of good quality, and 5 (11%) of poor quality. The quality of evaluations published in the past 15 years was higher (average 75%) than evaluations published prior to 2005 (average 58%), with the quality of evaluations varying by intervention-88% of EGDT and resuscitation protocol evaluations were of very good or excellent quality compared to 60% of evaluations of antibiotic therapies and 25% of evaluations of pathogen identification (Additional file 4).…”
Section: Reporting Qualitymentioning
confidence: 99%